Women Suffered More Emotional and Life Distress than Men during the COVID-19 Pandemic: The Role of Pathogen Disgust Sensitivity - Ding, Yi; Yang, Jie; Ji, Tingting; Guo, Yongyu (International journal of environmental research and public health, 2021)
The outbreak of the COVID-19 has brought upon unprecedented challenges to nearly all people around the globe. Yet, people may differ in their risks of social, economic, and health well-being. In this research, we take a gender-difference approach to examine whether and why women suffered greater emotional and life distress than men at the early stage of the COVID-19 outbreak in China. Using a large nationwide Chinese sample, we found that compared to men, women reported higher levels of anxiety and fear, as well as greater life disturbance during the COVID-19 pandemic. Importantly, that women suffered more was partly explained by their higher level of pathogen disgust sensitivity. Our findings highlight the important consequences of gender differences in response to the threat of the COVID-19 pandemic and suggest that policymakers pay more attention to gender inequalities regarding COVID-19 responses.